Silymarin Protects against Acute Liver Injury Induced by Acetaminophen by Downregulating the Expression and Activity of the CYP2E1 Enzyme - Weipei Yang; Zhongxu Liang; Chengming Wen; Xuehua Jiang; Ling Wang (Molecules, 2022)
Previous studies have shown that silymarin protects against various types of drug-induced liver injury, but whether the protective mechanism of silymarin against acetaminophen-induced liver injury is related to the CYP2E1 enzyme remains unclear. In this study, we investigated the effect of silymarin on the activity and expression of CYP2E1 in vitro and in vivo. The results of in vitro studies showed that silymarin not only inhibited the activity of CYP2E1 in human and rat liver microsomes but also reduced the expression of CYP2E1 in HepG2 cells. In vivo studies showed that silymarin pretreatment significantly reduced the conversion of chlorzoxazone to its metabolite 6-OH-CLX and significantly increased the t1/2, area under the curve (AUC) and mean residence time (MRT) of chlorzoxazone. In addition, silymarin pretreatment significantly inhibited the upregulation of Cyp2e1 expression, reduced the production of 3-cysteinylacetaminophen trifluoroacetic acid salt (APAP-CYS), and restored the liver glutathione level. The results of our study show that silymarin plays an important protective role in the early stage of acetaminophen-induced acute liver injury by reducing the activity and expression of CYP2E1, reducing the generation of toxic metabolites, and alleviating liver injury.